Motion And Grasping Control Method Of 2-Dof Robotic Finger - Md Ghazaly, Mariam; Mohamad Yuden, Mohamad Adzeem; Che Amran, Aliza (International Journals of Engineering and Sciences Publisher, 2019)
The focus of this paper is the grasping control and tracking performances for the two degrees of freedom (2-DOF) robotic finger mechanism in accomplishing precision motion control as the initial study in the development of a multi-fingered robotic hand system. In the robotic hand mechanism, behaviours like large steady-state error, instability, and poor transient performance are often observed. For this research, the proposed controllers will rely on each motor joint's angular position control, which refers to the position control possessed by the 2-DOF robotic finger mechanism. Three various control approaches namely (i) Fuzzy Logic controller (FLC) (ii) Proportional Integral Derivative (PID) controller and (iii) Linear Quadratic Regulator (LQR) controllers were selected for comparison via experimental and simulation works. Validation of the controller results was performed by tracking control and grasping control, with frequency ranges from 0.1 Hz to 0.5 Hz at various reference amplitudes. Based on the results of the analysis, it was concluded that LQR controller had the best performance for tracking control. The LQR controller exhibited a 98.5% (0.11 °) improvement in steady-state error compared to an uncompensated system based on a series of experimental tracking tests. Another conclusion was that the 2-DOF robotic finger mechanism was also successful in grasping tasks with the Fuzzy controller being used by the specific reference trajectory.